Neuroimaging in Antisocial Personality Disorder - Abdullah Yildirim; Derya Tureli (Psikiyatride Güncel Yaklaşımlar, 2015)
Neuroimaging has been used in antisocial personality disorder since the invention of computed tomography and new modalities are introduced as technology advances. Magnetic resonance imaging, diffusion tensor imaging, functional magnetic resonance imaging and radionuclide imaging are such techniques that are currently used in neuroimaging. Although neuroimaging is an indispensible tool for psychiatric reseach, its clinical utility is questionable until new modalities become more accessible and regularly used in clinical practice. The aim of this paper is to provide clinicians with an introductory knowledge on neuroimaging in antisocial personality disorder including basic physics principles, current contributions to general understanding of pathophysiology in antisocial personality disorder and possible future applications of neuroimaging. [Psikiyatride Guncel Yaklasimlar - Current Approaches in Psychiatry 2015; 7(1): 98-108]